Factors Influencing Midwife Practices in Antenatal Services in The Early Detection of High Risk Pregnancy in Serang District - Dwiyarina Margarisa; Bagoes Widjanarko; Tinuk Istiarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
In Serang regency for 2 last years occured increasing of mother dead. This case more take place at antenatal period than having birth and porturition period. Mother dead can be prevented if high risk pregnant mother detected early, on of the method by doing pregnancy checkup appropriate with 7T standart to the pregnant mother. This research has purpose to identify and analize factors that affect midwife practice in antenatal care of high risk pregnancy early detection at Serang Regency. This research is analitik description research with cross sectional approach. The research subjects were midwife that practice BPM by use sample 73 midwifes. Result of the research showed that 52.1% respondent didn’t do antenatal care on the high risk pregnancy early detection. Factors that related to midwife practice in antenatal care were age, education, long time of work and knowledge where result of statistic experiment was gotten p value < 0,05. Suggestion for IBI is increase monitoring and educating to its members, Health Department should be more distinct give a reward and punishment to BPM practice so that rescuing mother and baby more success, and for BPM should increase knowledges.